Control of flow deflection angle around the corner using microjet array - Yuto Nakadori; Satoshi Yuura; Takahiro Kagawa; Akira Urita; Taro Handa (Scientific Reports)
Abstract In this study, a new technique for active control of the flow around a corner is proposed and a key parameter dominating the flow deflection angle is proposed. In the technique, a microjet array is used for controlling the deflection of the flow at 33 m/s ~ 54 m/s around the 25-degree corner with a small downstream-facing step, the surface of which is lined with the micro-orifices from which jets are injected into the flow. The flow velocities around the corner are measured using a PIV (particle image velocimetry) technique under each condition for injecting the microjets into the flow. The results reveal that a vortex is produced by the microjet array and the flow past the corner is pulled into the low-pressure region near the vortex core, i.e., the flow that has passed the corner deflects downward to the vortex. The results also reveal that the flow deflection angle increases with the supply pressure, i.e., the deflection angle increases with the jet Mach number. In addition, a parameter in the form of a momentum coefficient is introduced for data reduction by considering that the flow deflection is induced by a Rankine’s combined vortex. As a result, the relationship between the momentum coefficient and the streamline slope is expressed by a single linear relation regardless of the flow speed, which suggests that the flow deflection angle is controllable precisely by using the microjet array.